AUDIO RELAKSASI MUSIK LULLABY TERHADAP KUALITAS TIDUR PADA ANAK USIA PRASEKOLAH (4-6 TAHUN) : STUDI DI TK TUNAS HARAPAN DESA SIDOMULYO KABUPATEN TRENGGALEK - Nila Ayu; Linda Ishariani; Melani Kartika Sari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Preschoolers aged 4-6 years need approximately 11 hours of sleep a day as a need for rest and sleep. But not all preschool age children are able to meet these needs so that the quality of their sleep is also not met properly. Relaxation music as a means to help children meet their sleep needs, especially sleep quality. This study aims to determine the effect of lullaby music relaxation audio on the sleep quality of preschool children (4-6 years) in Tunas Harapan Kindergarten, Sidomulyo Pule village, Trenggalek district. The design used in this research is "Pre Experiment one group pre-post test design". The population of this study were all students of Tunas Harapan Kindergarten, Sidomulyo village, Trenggalek district as many as 31 children with purposive sampling technique obtained a sample of 20 respondents. The research instrument used a questionnaire, with the statistical test used was the Wilcoxon test. The results of the study before being given the lullaby music relaxation audio intervention that most (70%) respondents experienced sleep quality with poor criteria. After the intervention, almost all (90%) of the respondents experienced a change in sleep quality with good criteria. From the results of statistical tests using Wilcoxon, it was found that before and after the intervention was given a sig (2-tailed) p-value of 0.005 <α = 0.05, which means that there is an effect of providing lullaby music relaxation audio intervention on sleep quality in children. Relaxation of lullaby music can stimulate the brain to reduce stress hormones and increase serotonin hormones so that the body becomes more relaxed. This study recommends that lullaby music relaxation audio music can be used as a lullaby for children in everyday life that can be applied in the community environment as well as in the nursery for children.